PENGEMBANGAN MODUL PROYEK KALBU (KAMI PENYELAMAT BUMI) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF - Khoirul Amri; Aan Widiyono (Balai Besar Guru Penggerak Jawa Timur, 2023)
This research aims to develop a project module to strengthen the profile of Pancasila students, knowing the feasibility, practicality and effectiveness of the module. The project module developed was named the KALBU (We Save the Earth) project module on the theme of sustainable lifestyle phase B grade IV elementary school. This research uses research and development methods. The development procedure uses the ADDIE development model (analysis, design, development, implementation, evaluation). The research was conducted in the second semester of the 2022/2023 academic year at SDN Puncel 01. The data collection instrument used questionnaires by experts, student and teacher response questionnaires, and rubik's assessments based on indicators of creative thinking skills. Data analysis uses qualitative and quantitative descriptive analysis. The feasibility test results of media experts get a percentage of 83.03% and material experts of 88.33%. These results show that the developed module is very feasible to use. The results of the practical test through student responses received a percentage of 92.73% and teacher responses of 93.73%. These results show that the modules developed belong to the very practical category. The results of the effectiveness test through improving creative thinking skills from the pre-test average score of 49.9 rose during the post-test of 85.9 with an N-gain value of 0.73 in the high category. That way the KALBU project module is effective in improving creative thinking skills. Abstrak Penelitian ini bertujuan untuk mengembangkan modul proyek penguatan profil pelajar Pancasila, mengetahui kelayakan, kepraktisan dan keefektifan modul. Modul proyek yang dikembangkan diberi nama modul proyek KALBU (Kami Penyelamat Bumi) pada tema gaya hidup berkelanjutan fase B kelas IV Sekolah Dasar. Penelitian ini meggunakan metode penelitian dan pengembangan. Prosedur pengembangan menggunakan model pengembangan ADDIE (analysis, design, development, implementation, evaluation). Penelitian dilaksanakan pada semester II tahun ajaran 2022/2023 di SDN Puncel 01. Instrumen pengumpulan data menggunakan angket oleh ahli, angket respon siswa dan guru, serta rubik penilaian berdasarkan indikator keterampilan berpikir kreatif. Analisis data menggunakan analisis deskriptit kualitatif dan kuantitatif. Hasil uji kelayakan ahli media mendapatkan persentase sebesar 83,03% dan ahli materi sebesar 88,33%. Hasil tersebut menunjukkan bahwa modul yang dikembangkan sangat layak digunakan. Hasil uji praktikalisasi melalui respon siswa mendapatkan persentase sebesar 92,73% dan respon guru sebesar 93,73%. Hasil tersebut menunjukkan modul yang dikembangkan termasuk kategori sangat praktis. Hasil uji efektifitas melalui peningkatan keterampilan berpikir kreatif dari pre-test rata-rata nilai sebesar 49,9 naik saat post-test 85,9 dengan nilai N-gain sebesar 0,73 dengan kategori tinggi. Dengan begitu modul proyek KALBU efektif dalam meningkatkan keterampilan berpikir kreatif.